Material Approaches to Exploring the Borders of Paratext - Ruokkeinen Sirkku; Liira Aino (The society for textual scolarship, 2022)
This paper studies the interplay of text and paratext using late medieval and early modern printed and manuscript sources. We argue that the paratext framework should include a distinction between the abstract and material notions of text, as it is the features of the material text which help identify intersections between text and paratext. Three elements, namely enlarged initials, notes, and type- and script-switches, are analysed to show how paratextual elements are often layered, and may have both textual and paratextual functions at the same time. What results is a complex network of elements in different textual and paratextual relationships.